RELATIVE IMPORTANCE OF THERMODYNAMIC AND KINETIC PROCESSES IN GOVERNING THE CHEMICAL AND ISOTOPIC COMPOSITION OF CARBON GASES IN HIGH-HEATFLOW SEDIMENTARY BASINS - Giggenbach W.F. (My University, 1997)
Application of techniques developed for the interpretation of fluid compositions in high-temperature hydrothermal or geothermal systems to lower-temperature natural gas discharges in New Zealand and the Gulf of Thailand showed that redox potentials, as reflected in relative CH4 and CO2 contents, are closely controlled by interaction with divalent and trivalent Fe in rock contacted by the fluids. In contrast to geothermal systems, where CO2 partial pressures approach equilibrium with respect to the conversion of Ca-Al-silicates to calcite and clay, absolute gas pressures in hydrocarbon reservoirs are governed by reservoir pressure. In high-heatflow, >80mW/m2, sedimentary basins, CH4, and CO2 approach both chemical and 13C-isotopic equilibrium, with the rate of attainment of isotopic equilibrium estimated to be some 400 times slower than that of chemical equilibration. Relative CH4, C2H6, and C3H8 concentrations are controlled by a kinetic processes corresponding to random breakage of CC bonds of more complex molecules. Short-distance variations in relative CH4 and CO2 contents of well discharges are largely due to underground vapor-liquid separation processes. The composition of gases from high-heatflow sedimentary basins suggests that they form in systems open to the escape of earlier formed products and to interaction with redox-active components of the host rock. In addition to oxidative degradation of organic material in contact with comparatively oxidising sedimentary material, interaction with highly reduced mafic rocks may give rise to reductive degradation or even synthesis of reduced C species.